Impact of candesartan on cardiovascular events after drug-eluting stent implantation in patients with coronary artery disease: The 4C trial. Issue 4 (April 2016) - Sakamoto, Tomohiro; Ogawa, Hisao; Nakao, Koichi; Hokimoto, Seiji; Tsujita, Kenichi; Koide, Shunichi; Yamamoto, Nobuyasu; Shimomura, Hideki; Matsumura, Toshiyuki; Oshima, Shuichi; Kikuta, Koichi; Oka, Hideki; et al.
Abstract: Objective: The purpose of this study was to examine the cardiovascular protective effects of candesartan in patients undergoing percutaneous coronary intervention (PCI) with drug-eluting stents (DESs). Background: Candesartan has been reported to reduce cardiovascular events when therapy was started 6 months after PCI with bare-metal stents in patients who survived restenosis. Candesartan started immediately after PCI with DESs was also effective in preventing cardiovascular events. Methods: The 4C trial was a multicenter, prospective, randomized, open-label study. A total of 1145 patients at 39 centers in Japan were randomly assigned to receive candesartan plus standard medical treatment or standard medical treatment alone. The primary endpoints were all-cause death, and a composite of non-fatal myocardial infarction (MI), unstable angina pectoris (uAP), congestive heart failure (CHF), and non-fatal cerebrovascular events. The follow-up period was up to 3 years after the index PCI (ClinicalTrials.govNCT00139386 ). Results: The incidence of total death, one of the primary endpoints, was comparable between the two treatment groups (3.8% each, p  = 0.9702). Another primary endpoint, non-fatal major cardiovascular events, tended to occur more often in the control group than in the candesartan group (9.2% vs. 12.5%, p  = 0.0985). In contrast, candesartan significantly reduced one of the pre-specified secondary endpoints: cardiovascular events that included non-fatal MI, uAP, and CHF (4.4% vs. 6.7%, p  = 0.0136). Furthermore, candesartan significantly reduced another secondary endpoint that included cardiovascular events and cardiovascular death (5.0% vs. 7.7%, p  = 0.0493). Conclusions: The 4C trial showed that candesartan administered immediately after PCI with DESs did not improve the prognosis after the index procedure, but did reduce some cardiac-related events for 3 years.